Ayurvedic Protocol on Effectiveness of Pippalyadi and Suranadi Ointment in Management of Arsha (Haemorrhoids) - Suraj Rathod; Kiran Khandare; Alok Kumar Diwedi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background- Ano-rectal disorders are progressively increasing in the society. Out of many of the causes, someimportant are sedentary lifestyle, irregular and inappropriate diet, prolonged sitting or standing and certainpsychological disturbances too. Arsha is one among the ano rectal diseases which occurs in Gudapradesha,which is a sadhyopranaharaMarma[1]. In Arsha bleeding per anum is the principal symptoms .Arsha is agift of modern diets and busy lifestyles and many people are suffering from some sort of Anorectal disorder,it may be simple constipation to complex carcinoma, in which prominent disorder is Arsha. It is manifesteddue to multifold factors viz. disturbed lifestyle or daily routines, improper or irregular diet intake, prolongedstanding or sitting, faulty habits of defecation etc. which results in derangement of Jatharagni leading tovitiation of Tridosha, mainly VataDosha.